Reconstruction of congenital microtia after ear canaloplasty using V-Y advancement of a temporal triangular flap - Hae Yeon Park (Korean Society of Plastic and Reconstructive Surgeons, 2021)
Background Reconstruction of congenital microtia remains challenging, particularly in patients with a history of ear canaloplasty due to insufficient regional soft tissue. The insertion of a tissue expander prior to implantation of the cartilage framework has traditionally been employed. However, this procedure could induce additional morbidity. Herein, we present a method using V-Y advancement of a temporal triangular flap to gain additional soft tissue in these challenging cases. Methods Congenital microtia patients with a history of ear canaloplasty who underwent auricular reconstruction using the Nagata technique between 2016 and 2020 were reviewed. To obtain additional soft tissue, V-Y advancement of a temporal triangular flap was performed concurrently with implantation of the costal cartilage framework, without prior insertion of a tissue expander. The outcomes of these patients with respect to postoperative complications and esthetics were evaluated. Results Eight patients with bilateral lesions were included. No specific complications developed after the first-stage surgery. However, one patient experienced complications after the second stage (auricular elevation). An analysis of the esthetic results showed most patients had excellent outcomes, achieving a satisfactory convolution. The median number of operations needed to complete reconstruction was 2, which was fewer than required using the conventional method with prior insertion of a tissue expander. Conclusions In patients with a history of previous canaloplasty, V-Y advancement of a temporal triangular flap could serve as an alternative to tissue expansion for microtia reconstruction. This technique provided reliable and satisfactory results with a reduced number of surgical stages.